A composite current collector
By using a support layer in the composite fluid collecting, its width elongation is greater than or equal to the heat shrinkage rate, combined with the high temperature environment of the vacuum cavity and the roller tension, the problem of insufficient thickness uniformity and bonding force of the metal layer is solved, and the battery performance and life are improved.
Patent Information
- Application Number
- CN202410768176.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The thickness uniformity of the metal layer in the existing composite fluid collecting fluid is inconsistent, and the bonding force between the metal layer and the plastic film layer is insufficient, which affects the battery performance.
A support layer is adopted, whose elongation in the width direction is greater than or equal to its heat shrinkage in the width direction, and by combining the tension of the roller in the high temperature environment of the vacuum cavity, the thickness uniformity and bonding force of the metal layer are improved.
The thickness uniformity and bonding force of the metal layer are improved, the service life of the battery is extended and the energy density is improved.
Smart Images

Figure CN118522903B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a composite current collector. Background Art
[0002] The composite current collector is a new type of current collector material composed of polymer materials and metals. It is used to gather current in batteries. Its structure is a "sandwich" structure with a plastic film layer in the middle and two surfaces in the thickness direction of the plastic film layer. There are metals on the two surfaces. Compared with traditional pure metal current collectors, composite current collectors have advantages in safety and potential cost-effectiveness.
[0003] However, the thickness uniformity of the metal layer on the surface of the composite current collector produced by current manufacturers is inconsistent, and the bonding strength between the metal layer and the plastic film layer is insufficient, which will affect the battery performance. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a composite current collector, aiming to improve the thickness uniformity of the metal layer in the composite current collector and improve product performance.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a composite current collector, which comprises a support layer, wherein a first metal coating is arranged in the thickness direction of the support layer, and the elongation of the support layer in the width direction is greater than or equal to its thermal shrinkage in the width direction.
[0007] In one embodiment, the elongation of the support layer in the width direction is 0.5%-5%, and the thermal shrinkage of the support layer in the width direction is less than or equal to 1%.
[0008] In one embodiment, the thermal shrinkage rate of the first metal coating layer is smaller than the thermal shrinkage rate of the support layer.
[0009] In one embodiment, an insulating coating is further included, wherein the insulating coating is disposed between the first metal coating and the support layer, and the thermal shrinkage rate of the insulating coating is greater than or equal to the thermal shrinkage rate of the support layer and greater than the thermal shrinkage rate of the first metal coating.
[0010] In one embodiment, it further includes a second metal coating layer, wherein the second metal coating layer is disposed on the surface of the first metal coating layer;
[0011] The first metal coating is a metal coating made of nickel alloy, copper alloy, aluminum alloy, titanium alloy, aluminum metal, copper metal, or titanium metal;
[0012] The second metal coating is a metal coating made of copper, aluminum, titanium, nickel or chromium.
[0013] In one embodiment, the sum of the thicknesses of the first metal coating and the second metal coating is 1 um.
[0014] In one embodiment, the first metal coating is a magnetron sputtering coating or a vacuum evaporation coating, and the second metal coating is a magnetron sputtering coating or a vacuum evaporation coating or an acid plating coating.
[0015] In one embodiment, the elongation of the support layer in the width direction specifically refers to: the degree of deformation of the support layer when a tensile force less than 1N is applied to the support layer in the width direction.
[0016] In one embodiment, the heat shrinkage rate of the support layer is obtained by:
[0017] The support layer was placed in an oven at 150° for 30 minutes, and the heat shrinkage rate of the support layer was obtained after measuring the dimensional changes of the support layer in the width and length directions.
[0018] In one embodiment, the support layer is a heat shrinkable film made of at least one material selected from the group consisting of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate.
[0019] Compared with the prior art, the present invention provides a composite current collector, including a support layer, a first metal coating is provided in the thickness direction of the support layer, and the elongation of the support layer in the width direction is greater than or equal to its thermal shrinkage in the width direction. The composite current collector of the present invention adopts a support layer whose elongation in the width direction is greater than or equal to its thermal shrinkage in the width direction, so that when the metal layer is prepared in the high temperature environment of the vacuum cavity, combined with the tension of the roller in the width direction of the support layer, the thickness of the metal layer is more uniform after the support layer is combined with the metal particles, and the metal layer is less likely to fall off, which is beneficial to the improvement of the energy density and service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained according to the structures shown in these drawings without creative work. In the drawings:
[0021] Figure 1 Schematic diagram of the structure of the composite current collector in an embodiment of the present invention. DETAILED DESCRIPTION
[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by the embodiments of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0023] It should be noted that when a component is referred to as being "fixed to" or "disposed on" another component, it can be directly on the other component or indirectly on the other component. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element. In addition, connection can be used for fixing or for circuit connection.
[0024] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0025] In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0026] The present invention provides a composite current collector, such as Figure 1As shown, the composite current collector includes a support layer 100, and the support layer 100 is provided with a first metal coating 201 in the thickness direction. The support layer 100 is used as the supporting body of the composite current collector. The support layer 100 has an upper and lower surface, and the first metal coating 201 is provided on both the upper and lower surfaces. The elongation of the support layer 100 in the width direction is greater than or equal to its thermal shrinkage rate in the width direction. Among them, the elongation of the support layer 100 in the width direction specifically refers to: the degree of deformation of the support layer 100 when the support layer 100 is subjected to a tensile force less than 1N in the width direction. The calculation method can be, first take a sample of the support layer 100 with a length of 100mm and a width of 15mm, then stretch it with a force of 1N in the width direction for 20 seconds, and then measure the width of the sample, subtract the value of 15mm before the measurement from the measured value, and then divide it by 15mm to obtain the elongation of the support layer 100 in the width direction.
[0027] During the preparation of the composite current collector, the inventors found through repeated experiments that when the support layer 100 is unfolded on the roller and the support layer 100 is driven forward by the rotation of the roller, especially when the support layer 100 is in a vacuum chamber and particles formed by magnetron sputtering or vacuum evaporation are attached to the support layer 100, due to the high temperature of the particles, a large amount of heat will be transferred to the support layer 100. Even if there is a cooling roller to cool the support layer 100, the heat generated will cause the support layer 100 to shrink thermally. At the same time, in the width direction of the support layer 100, since the support layer 100 runs on the roller, it will receive a tensile force in the width direction. If the tensile force in the width direction of the support layer 100 is less than the thermal shrinkage rate of the support layer 100, then after being heated, the support layer 100 will inevitably shrink inward, resulting in the metal particles being attached to the heated part of the support layer 100. The bonding force with the support layer 100 is loose and easy to fall off. In particular, when the support layer 100 is combined with the metal layer, it will shrink due to heat. When the support layer 100 is not combined with the metal layer, under the pulling force of the roller, the roller will expand the shrunk part of the support layer 100. After such shrinkage and expansion, the metal layer formed on the support layer 100 will be more likely to fall off, and the thickness will also be uneven.
[0028] The composite current collector of the present invention adopts a support layer 100 whose elongation in the width direction is greater than or equal to the thermal shrinkage rate in the width direction. When the metal layer is prepared in the high temperature environment of the vacuum cavity, combined with the pulling force of the roller on the support layer 100 in the width direction, the thickness of the metal layer is more uniform after the support layer 100 is combined with the metal particles. The metal particles are less likely to fall off when attached to the heated parts of the support layer 100, which is beneficial to improving the energy density and service life of the battery.
[0029] Preferably, in the composite current collector of the present invention, the elongation of the support layer 100 in the width direction is 0.5%-5%, and the thermal shrinkage of the support layer 100 in the width direction is less than or equal to 1%. The inventor has conducted unlimited tests and found that the use of the support layer 100 with the above-mentioned elongation and thermal shrinkage in the width direction can make the coating more uniform, and the coating and welding of the current collector can also heat the support layer 100, which is also conducive to the subsequent coating and tab welding on the current collector, making the tab welding more firm, thereby improving the battery performance and life.
[0030] Specifically, the support layer 100 is a heat shrinkable film made of at least one material selected from polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate. The support layer 100 is made of a film with corresponding heat shrinkage properties made of a polymer material, so that the thickness of the prepared metal layer is more uniform under the pulling force of other rollers, and is also conducive to subsequent coating and tab welding on the current collector.
[0031] Preferably, the heat shrinkage rate of the support layer 100 in the length direction is less than or equal to 3%, and the heat shrinkage rate in the width direction is less than or equal to 1%. In this way, the bonding force between the first metal coating 201 and the support layer 100 in the transverse and longitudinal directions of the support layer 100 can be improved. This is because the first metal coating 201 is usually formed by magnetron sputtering or vacuum coating, and the temperature of the above preparation method is relatively high. If the heat shrinkage rate is high, the surface of the support layer 100 will be wrinkled, which will cause the crystal nucleus of the first metal coating 201 to be unable to be well bonded to the surface of the support layer 100, so that the first metal coating 201 is easy to fall off. Therefore, the composite current collector of the present invention adopts a support layer 100 with corresponding heat shrinkage properties in the length direction and width direction, respectively, which improves the bonding force between the support layer 100 and the first metal coating 201, ensuring that the appearance and performance of the battery are not affected.
[0032] Preferably, the thermal shrinkage rate of the first metal coating 201 is less than the thermal shrinkage rate of the support layer 100. In the composite current collector in this embodiment, on the basis that the support layer 100 has corresponding thermal shrinkage characteristics, the thermal shrinkage rate of the first metal coating 201 is also less than the thermal shrinkage rate of the support layer 100, so that when the composite current collector is punctured, since the thermal shrinkage rate of the support layer 100 is higher, more support layers 100 will cover the punctured place, and the support layer 100 is not conductive, so that resistance is formed in this place. Therefore, the thermal shrinkage rate of the first metal coating 201 in the composite current collector is less than the thermal shrinkage rate of the support layer 100, which can make the composite current collector more easily form point resistance when punctured, making the battery safer.
[0033] Specifically, the heat shrinkage rate of the support layer 100 is obtained by the following method: the support layer 100 is placed in a 150° oven for 30 minutes, and the heat shrinkage rate is obtained after the dimensional changes of the support layer 100 in the width and length directions are detected. The heat shrinkage rate mainly refers to the volume change of thermoplastic materials due to the thermal expansion rate. The memory property of the heat shrinkage material enables it to shrink and wrap around the outer surface of the object when heated, playing the role of insulation, moisture-proof, sealing, protection and connection. In this embodiment, the detection of the heat shrinkage rate is carried out by measuring the shrinkage change of the material within a certain temperature range. Specifically, the test sample of the support layer 100 is placed in a 150° oven for 30 minutes, and the heat shrinkage rate is calculated after recording the dimensional changes of the test sample in the width and length directions. By using the support layer 100 with corresponding heat shrinkage characteristics in the length direction and the width direction, when a partial short circuit occurs and the battery heats up, the support layer 100 can shrink and wrap the pierced position to form a point resistance to improve the flame retardant effect.
[0034] Preferably, the composite current collector of the present invention further includes an insulating coating 200, and the insulating coating 200 is disposed between the first metal coating 201 and the support layer 100. The insulating coating 200 may be a metal oxide coating such as aluminum oxide, silicon oxide, titanium oxide, etc. In this embodiment, the insulating coating 200 is disposed on both the upper and lower surfaces of the support layer 100, and the first metal coating 201 is disposed on the surface of the insulating coating 200. The insulating coating 200 between the first metal coating 201 and the support layer 100 can effectively prevent the metal connection between the upper and lower surfaces of the current collector, prevent danger from occurring, and improve the safety of the product.
[0035] Further, the thermal shrinkage rate of the insulating coating 200 is greater than or equal to the thermal shrinkage rate of the supporting layer 100, and greater than the thermal shrinkage rate of the first metal coating 201. In the composite current collector of this embodiment, an insulating coating 200 with a higher thermal shrinkage rate is arranged between the supporting layer 100 and the first metal coating 201, and the thermal shrinkage rate of the insulating coating 200 is greater than or equal to the thermal shrinkage rate of the supporting layer 100, and greater than the thermal shrinkage rate of the first metal coating 201. In this way, when the composite current collector of the present invention is pierced by a sharp object and a short circuit occurs, and the local heat is high, the supporting layer 100 shrinks, and the insulating coating 200 also shrinks together. At this time, the thermal shrinkage rate of the first metal coating 201 is smaller, so it shrinks slowly, and the thermal shrinkage rate of the insulating coating 200 is higher. In this way, the insulating coating 200 will wrap up the pierced position to prevent the metal connection between the upper and lower surfaces of the current collector, and can effectively form a point resistance to prevent danger, further improve the flame retardant effect of the composite current collector, and make the battery using the composite current collector safer.
[0036] Preferably, the composite current collector of the present invention also includes a second metal coating 202, which is arranged on the surface of the first metal coating 201, wherein the first metal coating 201 is a magnetron sputtering coating or a vacuum evaporation coating, and the second metal coating 202 is a magnetron sputtering coating or a vacuum evaporation coating or an acid plating coating.
[0037] Specifically, the metal coating group formed by the first metal coating 201 and the second metal coating 202 is arranged on the upper surface and the lower surface of the support layer 100. Taking the upper surface as an example, when the composite current collector is formed, the first metal coating 201 can be first formed on the support layer 100 by vapor deposition. Of course, when there is an insulating coating 200, the insulating coating 200 is first formed on the support layer 100 before the first metal coating 201 is formed, and then the first metal coating 201 is formed on the insulating coating 200, and then the second metal coating 202 is formed on the first metal coating 201 by vapor deposition or other methods. Among them, the first metal coating 201 is a metal coating made of nickel alloy, copper alloy, aluminum alloy, titanium alloy, aluminum metal, copper metal, and titanium metal. The first metal coating 201 mainly plays the role of improving the adhesion between the second metal coating 202 and the support layer 100 material. The second metal coating 202 is a metal coating made of copper metal, aluminum metal, titanium metal, nickel metal, and chromium metal. The second metal coating 202 mainly plays the role of converging current. After the second metal coating layer 202 is formed on the support layer 100, a composite current collector with uniform metal layer thickness and good bonding strength can be obtained.
[0038] Preferably, the sum of the thicknesses of the first metal coating 201 and the second metal coating 202 is 1 um. In this embodiment, by controlling the sum of the thicknesses of the first metal coating 201 and the second metal coating 202 to 1 um, the mass of the composite current collector can be greatly reduced. The more lightweight the composite current collector is, the more beneficial it is, which helps to improve the mass energy density of the battery, which is crucial for manufacturing lightweight and energy-efficient battery products, and can significantly improve the volume energy density of the battery, which has a positive impact on improving the overall performance of the battery.
[0039] In a preparation process, the first metal coating 201 of the composite current collector of the present invention can be sprayed, rolled or bonded to the support layer 100 with an adhesive, or can be formed on the support layer 100 by magnetron sputtering, vacuum evaporation, etc. Magnetron sputtering and vacuum evaporation are both physical vapor deposition methods, wherein magnetron sputtering refers to: using plasma generated by rare gas to bombard the surface of the cathode target under the action of electric field and magnetic field, and then sputtering out molecules, atoms, ions and electrons on the surface of the target, and the sputtered particles are ejected toward the surface of the base film in a certain direction, and then a coating is formed on the surface of the base film. The advantages of using this method are: 1) the sputtering atom energy is high, and the adhesion between the film and the substrate is strong; 2) the film thickness is controlled by controlling the target current, and the controllability and repeatability are good; 3) the material components of the crucible heater will not be mixed, and the metal film layer has high purity and high quality. Vacuum evaporation means: melting the metal into liquid, forming metal vapor and starting to volatilize, and then condensing the atoms in the vapor to deposit and grow on the surface of the polymer material. The deposition rate of vacuum evaporation is 3-4 times that of magnetron sputtering, which can quickly make up the thickness of the metal coating. Its advantages are: 1) heating and melting, fast film formation rate and high efficiency; 2) evaporation and adhesion do not require a high voltage electric field, the equipment is relatively simple and easy to operate; 3) vacuum heating evaporation atoms have low momentum and the film thickness is uniform.
[0040] The first metal coating 201 in this embodiment is preferably formed on the support layer 100 by magnetron sputtering. Specifically, the insulating coating 200 of the composite current collector is prepared on the support layer 100 by magnetron sputtering, and the thickness of the insulating coating 200 is 10nm-30nm; then the first metal coating 201 is formed on the insulating coating 200 by the same method, and the thickness of the first metal coating 201 is 50nm-100nm; and then one or more vacuum evaporation or magnetron sputtering is used to form a second metal coating 202 of 800nm-950nm on the first metal coating 201, so that a coating with a thickness of 900nm-1500nm is formed on one of the surfaces in the thickness direction of the support layer 100. In the preparation process adopted in this embodiment, the above-mentioned multiple steps and a single process (magnetron sputtering or evaporation) can greatly reduce costs and reduce holes when forming the coating.
[0041] Alternatively, in another preparation process, the composite current collector of the present invention can be formed in the following manner: the first metal coating 201 can be sprayed, rolled or bonded to the support layer 100 with an adhesive, or can be formed on the support layer 100 by magnetron sputtering, vacuum evaporation, etc. Preferably, magnetron sputtering is used to form the support layer 100, and the plasma generated by the rare gas is used to bombard the surface of the cathode target under the action of the electric field and the magnetic field, thereby sputtering out the molecules, atoms, ions and electrons on the surface of the target, and the sputtered particles are ejected toward the surface of the base film in a certain direction, thereby forming a coating on the surface of the base film, and obtaining the insulating coating 200 of the present application. At this time, the thickness of the insulating coating 200 is 10nm-30nm. The same method is used to form a first metal coating 201 on the insulating coating 200. At this time, the thickness of the first metal coating 201 is 50nm-100nm, and then an acid plating method is used to form a second metal coating 202 of 800nm-950nm on the surface of the first metal coating 201, so that a coating of 900nm-1500nm is formed on one of the surfaces in the thickness direction of the support layer 100. Among them, acid plating refers to using phosphor copper balls as anodes in an electroplating tank, placing the phosphor copper balls in an anode bag made of titanium blue, and then immersing the entire anode bag in an acidic agent (acidic sulfuric acid solution: sulfuric acid 90-170g / L, copper ions 50-160g / L, chloride ions 30-60ppm), with the metal layer on the membrane surface as the cathode, and the membrane surface passes between the rollers under the agent tank liquid. The membrane surface is immersed in the agent to perform ion migration replacement. After obtaining electrons on the membrane surface, a copper layer will be formed. The copper accumulation layer thickness is 800-950nm, and the membrane passes at a speed of 3-5m / min.
[0042] In the first preparation process mentioned above, after obtaining the finished film, it is also necessary to cut, pack and ship it. In the second preparation process mentioned above, after acid plating, it is also necessary to perform anti-oxidation treatment, which specifically refers to letting the above-mentioned current collector after acid plating pass through an antioxidant tank, in which an antioxidant liquid is placed. After the current collector passes through the antioxidant liquid, antioxidant liquid will remain on the surface, and then the antioxidant liquid is dried to retain the possible components of the antioxidant liquid on the finished film, and then such a film is cut to achieve the width required by the customer. Preferably, it is also necessary to wash with water after acid plating to wash off the acid plating solution on the surface of the current collector to prevent the plating solution from contaminating the antioxidant liquid.
[0043] In the above two processes, an optical density tester can be added to the vacuum evaporation or magnetron sputtering. The optical density tester directly senses the transmittance or optical density of the film through optical contact, and uses a certain proportional relationship between the optical density and the coating thickness to detect the uniformity of the coating thickness. By adding an optical density tester to the vacuum evaporation or magnetron sputtering, the thickness of the coating formed on the support layer 100 can be detected online at any time. In this way, there is no need to open the cavity and then use a square resistance tester to detect the coating thickness, so that the coating thickness is accurately controllable, which effectively improves the preparation efficiency and performance reliability of the composite current collector.
[0044] In particular, if the first metal coating 201 is directly provided on the support layer 100, the preparation method of the first metal coating 201 can be formed on the support layer 100 by vacuum evaporation or magnetron sputtering to form a first metal coating 201 with a thickness of 10nm-500nm, and then the second metal coating 202 can be formed on the first metal coating 201 by magnetron sputtering, vacuum evaporation or acid plating. The thickness of the second metal coating 202 can be 100nm-500nm. The second metal coating 202 can be formed by multiple coatings or formed once, wherein the once-formed film has better bonding with the support layer 100, because the multiple-formed film is easy to fall off between the coatings, and the one-time forming method completes the coating in a vacuum chamber, without frequently opening and closing the vacuum chamber, which is more energy-saving and more efficient. At the same time, because there is no need to open and close the vacuum chamber, there is no process of transporting to the next workspace after production in multiple forming, so the coating can be avoided from being oxidized and the yield rate can be improved. When the second metal coating 202 is formed by acid plating, the thickness of the first metal coating 201 needs to be 300-500 nm to meet the requirements of subsequent acid plating, so as to avoid the difficulty of metallization of the second metal coating 202 and ensure the coating quality of the composite current collector.
[0045] The experimental data of the present invention are as follows: The experiment of the present invention includes a comparative sample and an experimental product. The experimental product is a composite current collector claimed for protection in this application, and its support layer is a heat shrink film made of PP film, so that the heat shrinkage rate of the heat shrink film in the transverse direction is less than 1%, and the elongation rate in the width direction of the support layer is between 0.5% and 5%. The thickness of the support layer is 6um, and the first metal coating is aluminum with a thickness of 1um. The conditions of the comparative sample and the experimental product are consistent, and the only difference is its elongation rate in the width direction and the heat shrinkage rate in the width direction. Then the following method is used to test the bonding strength between the coating and the film:
[0046] At room temperature and normal pressure, use 3M double-sided tape to evenly stick the sample on the stainless steel plate, and then evenly stick the sample to be tested on the double-sided tape. The length of the sample to be tested is 120 mm and the width is 50 mm. Then use a 500g roller to stick the sample firmly, and then use a 2 cm long and 12.7 mm wide 3M single-sided tape to stick on the sample to be tested, and then stick it firmly with a roller. Then use a high-speed rail tensile testing machine to peel off the conductive layer and the insulating layer of the sample to be tested. According to the data graph of tension and displacement, read the maximum tension, divide the read value by 0.02 (unit N), and calculate the metal layer strength, that is, the bonding force F between the current collector insulating layer and the conductive layer.
[0047] The following are the experimental data:
[0048]
[0049]
[0050] It can be seen from the above experimental data that: by comparing experimental product 1-3 with comparison sample 1-3, the binding force of experimental product 1-3 is greater than the binding force of comparison sample 1-3. The composite current collector of the present application effectively improves the binding force between the metal coating and the film, making the metal layer less likely to fall off, thereby increasing the product yield.
[0051] In summary, the present invention provides a composite current collector, comprising a support layer, a first metal coating is provided in the thickness direction of the support layer, and the elongation of the support layer in the width direction is greater than or equal to its thermal shrinkage in the width direction. The composite current collector of the present invention adopts a support layer whose elongation in the width direction is greater than or equal to its thermal shrinkage in the width direction, so that when the metal layer is prepared in the high temperature environment of the vacuum cavity, combined with the tension of the roller in the width direction of the support layer, the thickness of the metal layer is more uniform after the support layer is combined with the metal particles, and the metal layer is less likely to fall off, which is beneficial to the improvement of the energy density and service life of the battery.
[0052] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, several equivalent substitutions or obvious variations can be made without departing from the concept of the present invention, and the performance or use is the same, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A composite current collector, characterized in that: It comprises a supporting layer, wherein a first metal coating is provided in the thickness direction of the supporting layer, and the elongation of the supporting layer in the width direction is greater than or equal to the thermal shrinkage rate thereof in the width direction; The calculation method of the elongation of the support layer in the width direction is: take a support layer sample with an initial length value and an initial width value, stretch the support layer sample in the width direction with a force of 1N for 20 seconds, then measure the width of the sample, subtract the initial width value from the measured width value, and divide the measured width value by the initial width value to obtain the elongation of the support layer in the width direction; The first metal coating is a magnetron sputtering coating or a vacuum evaporation coating, and the thermal shrinkage rate of the first metal coating is smaller than the thermal shrinkage rate of the support layer; The elongation of the support layer in the width direction is 0.5%-5%, and the thermal shrinkage of the support layer in the width direction is less than or equal to 1%; The thermal shrinkage of the support layer is obtained by: The support layer is placed in an oven at 150° C. and baked for 30 minutes, and the thermal shrinkage rate of the support layer is obtained after measuring the dimensional changes of the support layer in the width and length directions; The support layer is a heat shrinkable film made of at least one material selected from the group consisting of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate.
2. The composite current collector according to claim 1, characterized in that: It also includes an insulating coating, which is arranged between the first metal coating and the support layer, and the thermal shrinkage rate of the insulating coating is greater than or equal to the thermal shrinkage rate of the support layer and greater than the thermal shrinkage rate of the first metal coating.
3. The composite current collector according to claim 1 or 2, characterized in that: Also comprising a second metal coating, the second metal coating being disposed on a surface of the first metal coating; The first metal coating is a metal coating made of nickel alloy, copper alloy, aluminum alloy, titanium alloy, aluminum metal, copper metal, or titanium metal; The second metal coating is a metal coating made of copper, aluminum, titanium, nickel or chromium.
4. The composite current collector according to claim 3, characterized in that: The sum of the thickness of the first metal coating and the second metal coating is 1 um.
5. The composite current collector according to claim 3, characterized in that: The second metal coating is a magnetron sputtering coating, a vacuum evaporation coating, or an acid plating coating.
Citation Information
Patent Citations
Composite current collector, pole piece comprising composite current collector and electrochemical device
CN116845248A